2022
DOI: 10.1093/mnras/stac199
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the architecture and internal structure of the TOI-561 system planets with CHEOPS, HARPS-N, and TESS

Abstract: We present a precise characterization of the TOI-561 planetary system obtained by combining previously published data with TESS and CHEOPS photometry, and a new set of 62 HARPS-N radial velocities (RVs). Our joint analysis confirms the presence of four transiting planets, namely TOI-561 b (P = 0.45 d, R = 1.42 R⊕, M = 2.0 M⊕), c (P = 10.78 d, R = 2.91 R⊕, M = 5.4 M⊕), d (P = 25.7 d, R = 2.82 R⊕, M = 13.2 M⊕) and e (P = 77 d, R = 2.55 R⊕, M = 12.6 R⊕). Moreover, we identify an additional, long-period signal (&a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 124 publications
1
11
0
Order By: Relevance
“…Most commonly, such long-period planets are often gas giants that form beyond the snowline of their system, and therefore represent an entirely different regime of both size and composition when compared to their close-in companions. For systems that instead contain ultra-short period (USP) members, such as TOI-561 (Weiss et al 2021;Lacedelli et al 2022), it has been shown that the USP planets are often markedly smaller than other members of the same system, and may have experienced a much more dynamically volatile formation history. (Winn et al 2018).…”
Section: All Planets Have Rv Mass Measurements With Fractionalmentioning
confidence: 99%
“…Most commonly, such long-period planets are often gas giants that form beyond the snowline of their system, and therefore represent an entirely different regime of both size and composition when compared to their close-in companions. For systems that instead contain ultra-short period (USP) members, such as TOI-561 (Weiss et al 2021;Lacedelli et al 2022), it has been shown that the USP planets are often markedly smaller than other members of the same system, and may have experienced a much more dynamically volatile formation history. (Winn et al 2018).…”
Section: All Planets Have Rv Mass Measurements With Fractionalmentioning
confidence: 99%
“…Sector 8 photometry featured two transits that Weiss et al (2021) interpreted as two transits of the same planet at 16.287 ± 0.005 days (giving a total of three transiting planets for the system), while Lacedelli et al (2021) interpreted it as single transits of two different planets (giving four transiting planets). Follow-up photometry from CHEOPS lifts this degeneracy in favor of the four-planet model, with planet d at an orbital period of 25.7124 ± 0.0002 days and planet e at a period of 77.03 ± 0.25 days (Lacedelli et al 2022). The additional TESS observations of Sectors 45 and 46 further support the four-planet model as described in Lacedelli et al (2022).…”
Section: Planet Radiimentioning
confidence: 60%
“…21 TOI-561 is 10 ± 3 Gyr old (Weiss et al 2021), making TOI-561 b one of the oldest known super-Earth-sized planets, indicating that rocky planets have been forming for nearly the age of the universe, even in metal-poor environments. Previous studies of this system suggest an even more unique aspect of this planet: it is the lowest-density super-Earth discovered to date, and potentially inconsistent with having a rocky planet composition (Lacedelli et al 2021(Lacedelli et al , 2022.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations